A new numerical method for the mechanical analysis of chopped carbon fiber tape-reinforced thermoplastics. (1st October 2018) - Qu, Peng; Wan, Yi; Bao, Chunjiang; Sun, Qun; Fang, Guangqiang; Takahashi, Jun
Abstract: Discontinuous carbon fiber-reinforced thermoplastics (DCFRTP) are promising materials for the fabrication of complex parts. In predicting the mechanical properties of DCFRTP with randomly oriented reinforcement, the application of numerical methods, which employ homogeneous models, is limited because the mesoscopic structural parameters influencing mechanical properties are not adequately represented in the macroscopic numerical model. On the basis of the peridynamic (PD) theory, a new numerical method, which employs a heterogeneous particle model, is proposed in this investigation for the mechanical analysis of DCFRTP. The tensile properties of ultra-thin chopped carbon fiber tape-reinforced thermoplastics (UT-CTT) are investigated using this numerical method. The relationship between PD horizon size and characteristic size of UT-CTT is discussed. The effect of model size on the scattering of the tensile properties is analyzed and the influence of interface properties on crack propagation is investigated. A comparison between PD simulations and experimental results indicated a good agreement.